Effect of adrenocorticotropin hormone and cortisol on epithelial sodium channels according to delivery route - Tezel, Gönül; Öztekin, Osman; Kalay, Salih; Akdağ, Mehmet; Turhan, Murat; Erin, Nuray; Akçakuş, Mustafa; Oygur, Nihal (Journal of Surgery and Medicine, 2019)
Aim: Immaturity of epithelial sodium channels (ENaC), which are affected by adrenocorticotropin hormone (ACTH) and cortisol, is believed to be the major underlying cause of transient tachypnea of the newborn. The aim of this study is to investigate the differences in ACTH and cortisol levels and the expression of lung ENaC α subunit of the babies in relation to mode of delivery. Methods: The study was planned as prospective cohort study. Eighteen women who underwent elective caesarean section (C/S) and fifteen women who admitted to hospital for normal spontaneous delivery (NSD) and their term 33 newborn infants were included in the study. Blood samples for ACTH and cortisol levels were collected from the mothers prior to birth and the newborn infants 1 hour after birth. Nasal mucosa species of the infants were performed to assess ENaC α subunit levels. Results: The ACTH and cortisol levels of mothers of C/S group were lower than the ACTH and cortisol levels of mothers of NSD group (p<0.001). Although the ACTH levels of infants delivered by C/S were significantly higher than the ACTH levels of infants delivered by NSD (p=0.001), no significant difference was identified between them with regards to the levels of cortisol (p=0.078) and ENaC α subunits (p:0.671). Conclusion: Our results suggest that hormonal mechanisms in newborn infants function independently from their mothers. In term babies mode of delivery is not the major factor affecting the expression of ENaC α subunit.